2003
DOI: 10.1123/ijsnem.13.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation Practices of Singaporean Athletes

Abstract: The supplementation practices of elite athletes in Singapore were studied using an anonymous questionnaire. Information was sought on not only the type of supplements used but also dosage, rationale for use, and other factors that might influence supplement use including selected demographic parameters and sources of information relating to supplements. Data was collected from 160 athletes across a spectrum of 30 sports. Use of supplements was widespread, with 77% of respondents acknowledging use of at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
2
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 37 publications
10
68
2
16
Order By: Relevance
“…The results of this study did not show significant correlation between mood disorders and AAS use which is different from the results of other studies that showed the higher prevalence of all mental disorders in AAS users except phobia, paranoia and psychosis (16). Also the AAS users had more often sought professional help for mental problems (10).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The results of this study did not show significant correlation between mood disorders and AAS use which is different from the results of other studies that showed the higher prevalence of all mental disorders in AAS users except phobia, paranoia and psychosis (16). Also the AAS users had more often sought professional help for mental problems (10).…”
Section: Discussioncontrasting
confidence: 57%
“…The mean reported prevalence in Iran is higher than developed countries (13). The knowledge level of young people, people with low education and people with little athletic experience about the side effects of AAS is very low (14,15); the rate of AAS usage has an indirect relation- ship with the individual's knowledge and education (16). Oxymetholone is the most common used drug in this category especially in Sweden (17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that 62 -80% of highperformance athletes under 20 years of age [188,190,209] and 51 -99% of all elite athletes use at least one dietary supplement [187,188,190,192,193,195].…”
Section: The Prevalence Knowledge and Attitudes Relating To Supplemementioning
confidence: 99%
“…caps. In addition, some researchers have also included, as supplements, coffee [197] and essence of chicken [193,196]. Whilst the majority of dietary supplements are taken by the general public to improve their health, athletes typically take supplements to enhance their training capacity and/or improve performance.…”
Section: The Prevalence Knowledge and Attitudes Relating To Supplemementioning
confidence: 99%
See 1 more Smart Citation